DAMPAK COVID TERHADAP PEREKONOMIAN SECARA MAKRO - Indri Arrafi Juliannisa; Nunuk Triwahyuningtyas; Charia Roswita (UNHI Press, 2021)
The spread of the Corona virus that has spread to various parts of the world has an impact on the Indonesian economy, both in terms of trade, investment and tourism. In Indonesia, the spread of this virus began on March 2, 2020, many sectors of the economy were affected by this pandemic. Thousands of companies were forced to temporarily close to limit the spread of the virus, resulting in reduced levels of activity in the arts, entertainment and recreation, as well as in real estate agencies and IT companies, however, there are some sectors of the economy that are still able to survive. If we compare it in the gold trading sector, the data shows a large increase in the estimated price for 2020 ytd of US 1,830 / troys ounce, even the prediction of the average price in 2021 also shows a constant increasing number. This is what has made the gold business popular because many people consider the price of gold to be more stable during this pandemic. Now the government is trying to open several business sectors and continues to encourage SMEs to carry out online activities, but still in the regions and gradually increase tax revenue. In order to maintain business continuity that saves the national economy, the government has implemented various socio-economic policy programs, including incentive policies and tax facilities that can be utilized by taxpayers. In order to maintain business continuity that saves the national economy, the government has implemented various socio-economic policy programs, including incentive policies and tax facilities that can be utilized by taxpayers. The government has also provided a policy on interest rates and airplane ticket prices so that people are still interested in visiting several discount cities for tourist destinations due to the existence of Covid-19 which has greatly impacted the tourism sector. The crisis due to Covid-19 is currently occurring simultaneously, so that the impact is felt by vulnerable groups who are getting worse, including business groups that need mass crowds, groups of casual daily workers, street vendors, workers affected by layoffs, farmers, the community poor, and so on.